Exploring the Affordances of ChatGPT in Developing Language Teachers’ Awareness and Pedagogical Practices - Tafazoli, Dara; McCallum, Lee (Journal of Language and Education, 2025)
Background: The field of language education is experiencing substantial advancements with the introduction of Generative Artificial Intelligence (GenAI). While there is a significant amount of research on teachers’ perceptions in language education, there is a noticeable gap in understanding the integration of ChatGPT into this field. Purpose: This study investigated the perceptions of EFL teachers in Iran regarding how ChatGPT can contribute to the enhancement of language teaching practices and pedagogical awareness. Method: A qualitative case study examined teachers’ perspectives on using ChatGPT in language education. A Zoom webinar on AI in teaching was conducted for Iranian EFL teachers, using tools like Focusky. From 73 registered teachers, 23 were selected based on ≥2 years’ teaching experience and voluntary participation. Data were gathered through focus groups, semi-structured interviews (n=10, in Persian), and reflective essays (n=10) submitted two weeks post-webinar. Inductive thematic analysis was performed using NVivo 12, with rigor ensured via peer debriefing, member checking, cross-case comparison, and 83% inter-coder agreement. Results: Data analysis revealed that ChatGPT can promote pedagogical awareness (i.e., enhanced professional development opportunities, enhancement of critical thinking skills, and autonomy and confidence) and pedagogical practices (i.e., understanding students’ needs and personalizing teaching and content creation and resource development). Conclusion: These findings suggest that ChatGPT can positively impact language teachers without necessarily sacrificing their jobs, which is the dominant concern in the current academic literature.